'Fabrics of Enchantment': Shelley's Use of the Venetian Setting in Julian and Maddalo. (2nd January 2017) - Dowling, Gregory
Abstract: The paper considers to what extent Shelley's poem Julian and Maddalo can be considered as providing a key to the relationship between Shelley and Byron. While most criticism has focused on the three central figures, with recent studies analysing the figure of the Maniac, to see whether he can be considered a disillusioned Shelleyan optimist or a Byronic hero taken to extremes, this paper examines more particularly the Venetian setting. The curiously illusory appearance of the city and its buildings, pictured as 'fabrics of enchantment piled to heaven', and the continuous alternation between images of darkness and light, all contribute to an overall atmosphere of ambiguity, within which it appears difficult to affirm any clear moral or intellectual principles. For this reason there is no clear winner in the debate between the two main characters, and the poem remains radically unsettled in both form and style, and unsettling in its implications.